Employment Status as a Predictor of Breastfeeding Self-Efficacy - Rini Mustikasari Kurnia Pratama; Damayanti Damayanti; Festy Mahanani Mulyaningrum; Bella Pratiwi Kurnia Pratama (Poltekkes Kemenkes Palu, 2026)
Background: In Indonesia, the percentage was 71.58% in 2021, and in the Province of Bengkulu in 2022, 67.85% of babies aged 0-5 months received exclusive breast milk. Around 32.15% of babies are still not breastfed. Breastfeeding with high self-confidence to successfully breastfeed their babies (breastfeeding self-efficacy) will influence the success of exclusive breastfeeding. The mother’s belief that her breast milk production is inadequate or little, which leads to worries that it won’t be sufficient to satisfy the baby’s demands, is the issue with not providing exclusive breastfeeding. This study aimed to identify factors that predict breastfeeding self-efficacy. Methods: The research design uses a cross-sectional analytical survey. The study population comprised 556 respondents, selected from a 100-person sample using the inclusion and exclusion criteria. The research period is from May to November 2024. Data collection uses a questionnaire with the BSES-SF. Data analysis uses discriminant analysis. Results:.The research results on the variables age (0.442), education (0.406), parity (0.575), ANC visits (0.165), and breastfeeding status (0.455), so there is no different in average age, education, parity, ANC visits, and breastfeeding status between self-efficacy in low and high breastfeeding mothers, while the working status variable has a p-value of 0.025, so there is a difference in the average working status between low and high self-efficacy. Conclusion: Mothers' working status as a predictor of breastfeeding self-efficacy.